2017
DOI: 10.1172/jci93825
|View full text |Cite
|
Sign up to set email alerts
|

YAP/TAZ regulates sprouting angiogenesis and vascular barrier maturation

Abstract: Angiogenesis is a multistep process that requires coordinated migration, proliferation, and junction formation of vascular endothelial cells (ECs) to form new vessel branches in response to growth stimuli. Major intracellular signaling pathways that regulate angiogenesis have been well elucidated, but key transcriptional regulators that mediate these signaling pathways and control EC behaviors are only beginning to be understood. Here, we show that YAP/TAZ, a transcriptional coactivator that acts as an end eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
337
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(358 citation statements)
references
References 78 publications
20
337
1
Order By: Relevance
“…Tek-Cre mice have been widely used for retinal vascular research. [32][33][34] Consistent with a previous study, 35 the ECs in the tip of the vascular front region of YAP cKO mice exhibited a blunted end with fewer dysmorphic filopodia ( Figure 2B). Since a previous study showed that TAZ cKO mice appeared normal and had no obvious vascular phenotype, the current study examined YAP cKO mice, which exhibit a gene dose-dependent dysfunctional vascular phenotype.…”
Section: Yap Is Required For Retinal Vessel Development and Parallesupporting
confidence: 90%
“…Tek-Cre mice have been widely used for retinal vascular research. [32][33][34] Consistent with a previous study, 35 the ECs in the tip of the vascular front region of YAP cKO mice exhibited a blunted end with fewer dysmorphic filopodia ( Figure 2B). Since a previous study showed that TAZ cKO mice appeared normal and had no obvious vascular phenotype, the current study examined YAP cKO mice, which exhibit a gene dose-dependent dysfunctional vascular phenotype.…”
Section: Yap Is Required For Retinal Vessel Development and Parallesupporting
confidence: 90%
“…Third, the Krt10 null mouse exhibits an intriguing phenotype of hyperproliferation, faster keratinocyte transit time, and impaired differentiation in the epidermis which, molecularly, correlates with a marked upregulation of 14-3-3sigma and c-Myc (Reichelt and Magin 2002;Reichelt et al 2004). MYC has since then been shown to be a bona fide YAP1 target gene (Schutte et al 2014;Kim et al 2017;Cai et al 2018). Possibly, therefore, K10 could extend the role of K14 as keratinocytes progress through terminal differentiation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a reduction of intermediate vascular plexus without any blood leakage in 12-month-old Yap +/retinal flat-mounts compared to controls (Supplementary Figure S13B and Supplementary Figure S14). Although recent studies have shown that YAP/TAZ are involved in vascular retinal development (Kim et al, 2017), no differences could be observed after labelling the three capillary plexi between 8-month-old Yap +/mice and controls (Supplementary Figure S13B). Such observation ruled out significant developmental defects of vascular networks.…”
Section: Deregulation Of Genes Important For Müller Cells Homeostasismentioning
confidence: 83%